Common Costs, Fixed Charges, Clubs and Games - Littlechild, S. C. (Review of Economic Studies, 1975)
unify these various approaches. We establish under what conditions a system of fixed charges exists to decentralize the optimal pattern of production (or club membership), characterize that system of charges and explore the relationship between the form of the common cost function and the optimal pattern of activities. More precisely, we show that in the absence of consumption externalities, and allowing part-time clubs,